Induced Mutation And Selection Of A High Yielding Strain Of Micrococcus Glutamicus For L-Lysine Production - A. GUPTA; S. K. DAS; A. K. BANIK (International Journal of Pharma and Bio Sciences, 2012)
The objective of this investigation was to develop a new auxotropic mutant from a regulatory mutant and to examine its potency for L-lysine production. A high L-lysine yielding strain Micrococcus glutamicus AB200 was developed from a regulatory mutant Micrococcus glutamicus AB5 by subsequent mutagenic treatment with UV rays and methyl methane sulfonate respectively. Treatment of UV rays on the regulatory mutant AB5 resulted in a mutant strain AB50 gives the maximum yield of L-lysine (5.5mg/mL) than the regulatory mutant (0.9 mg/mL). The mutant strain AB50 on further treatment with a chemical mutagen methyl methane sulfonate resulted to another mutant Micrococcus glutamicus AB200 which produced the highest yield of L-lysine (7.2mg/mL) Micrococcus glutamicus AB200 was an auxotropic mutant which requires biotin for growth as well as production of L-lysine. The L-lysine producing capacity of auxotropic mutant was tested after maintaining the strain in three different media of which the mutant was stable in a media having the composition of 5% glucose, 0.6% urea, 0.2% K2HPO4. 0.025% MgSO4. 7H2O, 2µg/mL biotin.